2022
DOI: 10.1021/acschembio.2c00400
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling-Based Chemoproteomics Establishes Choline Metabolites as Protein Function Modulators

Abstract: Choline is an essential nutrient for mammalian cells. Our understanding of the cellular functions of choline and its metabolites, independent of their roles as choline lipid metabolism intermediates, remains limited. In addition to fundamental cellular physiology, this knowledge has implications for cancer biology because elevated choline metabolite levels are a hallmark of cancer.Here, we establish a mammalian choline metabolite-interacting proteome by utilizing a photocrosslinkable choline probe. To design t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Separately, other fates of choline may be modified by or play a role in mediating the alteration of immune cell function. For instance, phosphocholine may post-translationally modify proteins [ 75 , 76 ], and macrophages and other immune cells have been shown to produce acetylcholine [ 77 ]. Conversion of choline to betaine may also support osmoregulation [ 78 ] or contribute to histone methylation [ 79 ], but these latter mechanisms require deeper investigation in immune contexts and remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, other fates of choline may be modified by or play a role in mediating the alteration of immune cell function. For instance, phosphocholine may post-translationally modify proteins [ 75 , 76 ], and macrophages and other immune cells have been shown to produce acetylcholine [ 77 ]. Conversion of choline to betaine may also support osmoregulation [ 78 ] or contribute to histone methylation [ 79 ], but these latter mechanisms require deeper investigation in immune contexts and remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, other fates of choline may be modified by or play a role in mediating the alteration of immune cell function. For instance, phosphocholine may post-translationally modify proteins, 71,72 and macrophages and other immune cells have been shown to produce acetylcholine. 73 Conversion of choline to betaine may also support osmoregulation 74 or contribute to histone methylation, 75 but these latter mechanisms require deeper investigation in immune contexts and remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a central underlying assumption that this technology relies on is that the probes employed retain stability in cells. This assumption is not always correct as demonstrated by our recent work [57] wherein we reported that mammalian cells convert alkynyl β-diazirine choline metabolic probes into their diazirine-devoid alkynyl choline derivatives. Therefore, meticulous metabolomics experiments aimed at characterizing the metabolic fates of these probes are imperative, as, if the photo-crosslinkable probes intended for use in chemoproteomic workflows are transformed into metabolic derivatives that are structurally distinct from the original probes, the results of the ensuing proteomics studies will report on the proteins that interact with these unintended metabolic derivatives rather than with the original probe, rendering the study erroneous.…”
Section: Photoaffinity Labeling Coupled With Mass Spectrometrymentioning
confidence: 90%
“…[49f] Another recent example of a photoaffinity labeling-based chemoproteomics study that yielded novel insights into the physiological roles of cellular metabolites focused on the discovery of mammalian proteomes that interact with the metabolites of the choline lipid biosynthesis pathway (the Kennedy pathway), namely, choline, phosphocholine, CDP choline and the lipids, phosphatidylcholine and sphingomyelin. [57] This work entailed the development of a bifunctional alkynyl diazirine choline analog adept at metabolically labeling choline metabolites (including lipids), and resulted in the identification of more than 600 choline metabolite-interacting mammalian proteins, including p32, a protein that plays a crucial role in cancer progression. Studies on p32 revealed that the choline metabolite, phosphocholine, profoundly modulates its binding with endogenous binding partners.…”
Section: Photoaffinity Labeling Coupled With Mass Spectrometrymentioning
confidence: 99%